Framing Analysis in the Papua Conflict in Benar News and The Guardian - Nur Hidayat Hadi Saputra; Frans Sayogie (Universitas Sanata Dharma, 2025)
The conflict in Papua has been ongoing since 1963 due to the Papuans' intention for independence. This conflict has been reported in many news media. Two news media outlets, Benar News and The Guardian, use framing when reporting issues related to the conflict in Papua. The framing in Benar News and The Guardian shapes the perceptions toward the issue of the Papua conflict. Accordingly, this study aims to explore the use of framing analysis in Benar News and The Guardian while reporting the problem related to the conflict in Papua and the depiction shown by Benar News and The Guardian when reporting the conflict in Papua. Using qualitative methods, this study applies Robert Entman's framing analysis approach, supported by text analysis in critical discourse analysis (CDA) by van Dijk, to analyze the data taken from two news outlets about the release of the pilot as one of the conflicts in Papua in Benar News and The Guardian. The findings reveal that Benar News and The Guardian frame the issue corresponding to the news. Benar News depicts the event as the Indonesian authorities' effort to release the pilot, who is captivated and taking a side toward Indonesia. Besides that, The Guardian depicts the issue as how the Papuan separatists face a struggle to gain independence that makes them kidnap the pilot as a bargaining chip, but heroically value human rights by releasing the pilot. Then, The Guardian takes a side toward the Papuans. This brings the idea that framing analysis supported by text analysis in CDA reveals how the news media present the issue to audiences. Therefore, the application of framing analysis supported by CDA's text analysis indicates that Benar News and The Guardian examine framing when reporting the issue of the Papua conflict according to their view.